Phytopharmaceutical Approach in the Development of Red Ginger (Zingiber officinale var. rubrum) Ointment for Inflammation and Pain Management - Raissa Fitri; Grace Anastasia Br Ginting; Fanny Asdian; Destina Karinia Siahaan; Sulistia Nurfadilla; Adiansyah Adiansyah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Red ginger (Zingiber officinale var. rubrum) is a variant of Z. officinale distinguished by its elevated levels of phenolic compounds—particularly gingerols, shogaols, and zingerone—that exhibit potent anti-inflammatory and analgesic effects. Topical formulations enable localized drug delivery, reducing systemic exposure and minimizing adverse effects commonly associated with oral nonsteroidal anti-inflammatory drugs (NSAIDs). Methodology: Dried red ginger rhizomes were powdered and extracted with 70% ethanol via maceration. The concentrated extract was incorporated into a white soft paraffin–lanolin base to produce ointments containing 5%, 10%, and 15% w/w extract. The formulations were assessed for physicochemical stability, including organoleptic characteristics, pH, spreadability, adhesion, and homogeneity. Anti-inflammatory activity was evaluated using the carrageenan-induced paw edema model in Wistar rats (n = 6 per group), with blank base and diclofenac sodium ointment (1% w/w) serving as negative and positive controls, respectively. Findings: All ointments exhibited stable physicochemical properties within pharmacopeial acceptance limits (pH 5.2–5.9; spreadability 5.6–6.4 cm; adhesion >1 s). In vivo, red ginger ointments significantly reduced paw edema in a dose-dependent manner (p < 0.05). The 15% formulation achieved 60.8% inhibition (0.47 ± 0.05 mL at 5 h), comparable to diclofenac ointment (0.48 ± 0.06 mL; p = 0.71). Contribution: The study establishes that red ginger retains pharmacological activity when formulated into a topical base, confirming its potential as a stable, safe, and effective phytopharmaceutical for localized inflammation management. These findings support further preclinical and clinical studies toward its development as a natural alternative to synthetic topical NSAIDs